Automatic detection of bumblebees using video analysis (2014)
In this document, we explore and develop techniques to automatically detect bumblebees flying freely inside a greenhouse, where illumination conditions are left unconstrained, and no artifact is used on their bodies. Specifically, we compare a Viola-Jones classifier and a Support Vector Machine (SVM) classifier to detect the presence of bumblebees. Our results show that the latter has a better classification performance.